Analisis Sistem Pengendalian Internal Terhadap Tingkat Piutang Pada Perusahaan Daerah Air Minum (PDAM) Tirta Silaupiasa Kabupaten Asahan - Elvina Damayanti; Rahmat Daim Harahap (CV. Ulil Albab Corp, 2022)
This study aims to analyze the control of accounts receivable at the company Tirta Bukae Drinking Water Area, North Luwu Regency and to find out how mucheffectiveness in collecting receivables to convert them into cash. The analytical methodused in this study, namely the analysis of accounts receivable turnover, analysis of the average agereceivables. Based on the results of the study, it can be concluded that PDAM Asahan RegencyNorth Luwu has not been effective in managing its receivables. This is evidenced by the resultscalculation of the average age of receivables from 2018 to 2021 which is not appropriate with the standard for collecting receivables that have been set by the PDAM, which is above 20 days,and the level of receivables turnover which is still very high.